Occupational Therapy's Role in the Foster Care System - Melanie N. Smith (Scholarworks @ WMU, 2022)
Children and youth who spend time in the foster care system face a variety of obstacles perpetuated by childhood trauma and limitations in service provision. Literature regarding this population demonstrates challenges, including the inability to form attachments and productive peer relationships, deficits in cognition and educational performance, and unpreparedness upon transitioning from the system. In addition, literature demonstrates the significantly increased prevalence of mental health challenges among those in foster care. Parents of foster children report inadequate services and supports to address the ongoing ramifications of a child raised in a constant state of traumatic stress. Following a depiction of the challenges, a solution in the form of occupational therapy services is demonstrated in this paper. The distinct value of occupational therapy is presented along with implications for this population in the scope of practice, thus highlighting an opportunity to expand service provision in this regard. This Opinions in the Profession paper seeks to demonstrate the possibility and importance of establishing a permanent role for occupational therapy in the child welfare system by presenting a review of several challenges at various levels in the system followed by a detailed depiction of the profession's role in this future opportunity.